Sosiologi politik : pengantar kritis / Keith Faulks ; penerjemah, Helmi Mahadi, Shohifullah ; penyunting, M. Khozim, Sufyanto - FAULKS, Keith; Khozim, M.; Sufyanto (Nusa Media, 2012)
xi, 364 hlm. ; 21 cm